Extending eligibility for general practitioner care in Ireland: Cost implications - Sheelah Connolly; Conor Keegan; Seamus O'Malley; Mark Regan (The Economic and Social Research Institute (ESRI), 2023)
Unlike most European countries, a majority of the population in Ireland pay out of pocket for a range of primary-care services, including general practitioner (GP) care. In 2017, the Committee on the Future of Healthcare published its final report (the Sláintecare Report; Houses of the Oireachtas Committee on the Future of Healthcare, 2017) recommending significant reforms for the health-care system including the introduction of universal GP and primary care. In Ireland, a GP visit card entitles people to GP visits that are free at the point of use. Currently in Ireland, there are two ways to be eligible for a GP visit card: age and income. Children younger than six and people aged 70 and over are entitled to a GP visit card on the grounds of age, while eligibility for other age groups is dependent on income. The aim of the research in this report is to estimate the demand and cost implications of extending eligibility for GP services (providing a GP visit card) to the whole population. The research examines the cost to the State of alternative approaches to extending eligibility between 2023 and 2026.
Keywords: 330; Gesundheitskosten; Gesetzliche Krankenversicherung; Basisgesundheitsversorgung; Ärzte; Irland